Photonic gas sensors exploiting directly the optical properties of hybrid carbon nanotube localized surface plasmon structures - Allsop, Thomas P.; Arif, Raz N.; Neal, Ron; Kalli, Kyriacos; Kundrát, Vojtěch; Rozhin, Aleksey; Culverhouse, Phil; Webb, David J (My University, 2016)
We investigate the modification of the optical properties of carbon nanotubes (CNTs) resulting fromachemical reaction triggeredbythe presence of a specific compound (gaseous carbon dioxide (CO2)) and show this mechanism has important consequences for chemical sensing. CNTs have attracted significant research interest because they can be functionalized for a particular chemical, yielding a specific physical response which suggests many potential applications in the fields of nanotechnology and sensing. So far, however, utilizing their optical properties for this purpose has proven to be challenging. We demonstrate the use of localized surface plasmons generated on a nanostructured thin film, resembling a large array ofnano-wires, to detect changesin the optical properties of the CNTs. Chemical selectivity is demonstrated using CO2 in gaseous form at room temperature. The demonstrated methodology results additionally in a new, electrically passive, optical sensing configuration that opens up the possibilities of using CNTs as sensors in hazardous/explosive environments.
Keywords: Carbon nanotubes; Gas sensors; Localized surface plasmons; Optical sensing